Problems and Solutions of Water Disinfection in Tashkent City - Javohir, Ozodjonov; Javlon, Alimukhamedov; Askar, Babayev (Research Parks Publishing LLC, 2023)
Waste water decontamination was considered on the example of the city of Tashkent. An analysis of the change of Escherichia coli in wastewater treatment with temperature is presented.